Analysis of student's obstacles on Biology learning assessment courses. Issue 4 (March 2020) - Sari, N I; Ahmar, D S; Ahmad, F
Abstract: Learning difficulty is an obstacle faced by students in achieving learning progress. One of the causes of learning obstacle is limited knowledge of students to certain concepts. The study aims to describe the students' learning obstacle through an in-depth analysis of learning process on Biology Learning Assessment course. The research design was qualitative with descriptive analysis method. The subject of the study was semester IV students of Biology Education at STKIP Pembangunan Indonesia academic year 2018-2019, which programmed Biology Learning Assessment course. The researcher collected the data through Respondent Ability Test (TKR) and interview. The results showed that the characteristics of student learning obstacles were complication in comparing the cognitive area on Bloom Taxonomy before and after revisions, obstacles in identifying and classifying relevant cognitive ability with learning objective, and the students had limitation designing questions by using operational verbs which suitable for Bloom Taxonomy revision.